Spanish adaptation and validation of the Cultural Competence Assessment Tool (CCATool) for undergraduate nursing students - Vázquez-Sánchez, María Ángeles; Casals-Vázquez, Alicia; Sánchez-Ojeda, María Angustías; García-Gámez, Marina; Papadopoulos, Irena; Casals, Cristina (Wiley, 2022)
Aim To analyse and validate a contextually adapted version of the Papadopoulos’ Cultural Competence Assessment Tool (CCATool) for Spanish undergraduate nursing students Background Globalization has driven and intensified international migration. Thus, nurses must treat patients of many different cultural origins. Accordingly, both cultural competence and an appropriate tool with which to evaluate it are required. Methods The CCATool questionnaire was adapted for use in a Spanish context and was evaluated through a questionnaire completed by 262 undergraduate nursing students. Seven days later, the same students completed the questionnaire, without any intervention, and a subgroup of 144 students completed the questionnaire for a third time after taking a course in Transcultural Care. The reliability, sensitivity and stability of the questionnaire were assessed. Results The reliability of the questionnaire obtained an adequate Cronbach's alpha of 0.81. Stability was assessed at seven days, using the intraclass correlation coefficient, which showed good/excellent results. Moreover, the questionnaire was able to detect the changes related to the nursing educative programme, thus highlighting a good sensitivity of the tool. Conclusion Cultural competence is an essential element of nurses’ education, and instruction in this area should begin as soon as possible. In addition, an appropriate evaluation system is required. For this purpose, the present study describes and analyses a valid, reliable tool for use with undergraduate nursing students in Spain. (...)
Keywords: Enfermería; Cultural competency; Culturally competent care; Health care; Nursing education; Nursing education research; Spain; Transcultural nursing; Validation studies